ANALISIS KERUGIAN DAN PEMETAAN SEBARAN SERANGAN RAYAP PADA BANGUNAN SD NEGERI DI BAGIAN BARAT KOTA PEKANBARU - Frisco Panahatan S; Yunus Afifuddin; Lutfhi Hakim (Program studi Kehutanan USU, 2015)
As one of the common facilities, Elementary Schools are very important and should be maintained in order to remain in good condition. Termites attacked on the building at the moment was a very big deal considering that the higher the intensity of their attacked and expanded so that the value of lost due to termite attacked tend to increase from year to year. This study aimed to get the value of economic losses termite attacked and get a map of the distribution of species of termites in the Elementary School building in the western of Pekanbaru. The research was conducted from July 2014 until August 2014 by using purposive sampling method 15% of the total number of Elementary Schools in the city of Pekanbaru. Data collected by direct observation and field interviews using questionnaires. The data obtained were then mapped using GIS (Geographic Information System). The results obtained showed that minor damage by 60% and were 40% moderate damage. Economic losses termites attacked against the State Elementary School building is Rp334.130.000 for tembesu wood standard and Rp246.367.000 for meranti wood standard. Types of termites that attacked the Elementary School Buildings were Microtermes inspiratus for subterranean termites and Cryptotermes cynocephalus for dry wood termites. Keywords: Termites, economic losses, school buildings, GIS